Penyelesaian Kredit Bermasalah Pada Perjanjian Kredit Perbankan karena Force Majeure di Masa Pandemi Covid-19 dalam Perspektif Peraturan Otoritas Jasa Keuangan Nomor 48/POJK.03/2020 - Tumanggor , M.S.; Putri, Elfirda Ade; Wulansari , Susi (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
A bank credit agreement is a standard agreement whose contents are determined unilaterally by the bank, with the aim of efficiency. Micro, small, and medium enterprises have an important role in economic development and growth. Small and medium enterprises often enter into banking credit agreements for business development. Due to the COVID-19 pandemic, the Indonesian government issued Presidential Decree No. 12 of 2020 stipulating the Determination of Non-Natural Disasters for the Spread of Corona Virus Disease 2019 (COVID-19) as a National Disaster. COVID-19 has had an impact on aspects of people’s lives. One of them has an impact on the decline in the economic capacity of the community which in turn can result in the debtor not fulfilling the achievements in the banking credit agreement. This study uses a normative juridical research method. The data collection method that the author uses is a literature study/documentation, namely data collection in a literature/document study is an activity of tracing, checking, and reviewing secondary data. The results of the research on the implementation of banking credit agreements are the fulfillment of the contents of the agreement in the form of implementation and obligations that have been agreed upon in the banking credit agreement. The COVID-19 pandemic has affected the implementation of banking credit agreements. The COVID-19 pandemic affects the ability of debtors to carry out their achievements. The government through the OJK issued POJK Number 48/POJK.03/2020, which is a regulation to provide restructuring to debtors. The COVID-19 pandemic can also be used as an excuse for debtors to experience force majeure. However, not all debtors are categorized as experiencing force majeure.